Viral haemorrhagic fever and vascular alterations - Aleksandrowicz, P.; Wolf, K.; Falzarano, D.; Feldmann, H.; Seebach, J.; Schnittler, H. (Hämostaseologie, 2008)
Pathogenesis of viral haemorrhagic fever (VHF) is closely associated with alterations of the vascular system. Among the virus families causing VHF, filoviruses (Marburg and Ebola) are the most fatal, and will be focused on here. After entering the body, Ebola primarily targets monocytes/ macrophages and dendritic cells. Infected dendritic cells are largely impaired in their activation potency, likely contributing to the immune suppression that occurs during filovirus infection. Monocytes/macrophages, however, immediately activate after viral contact and release reasonable amounts of cytokines that target the vascular system, particularly the endothelial cells.Some underlying molecular mechanisms such as alteration of the vascular endothelial cadherin/catenin complex, tyrosine phosphorylation, expression of cell adhesion molecules, tissue factor and the effect of soluble viral proteins released from infected cells to the blood stream will be discussed.
Keywords: Haemorrhagic fever